Navigating the landscape of the unfolded protein response in CD8+ T cells - Nair, Keith Alan; Liu, Bei (Frontiers in Immunology, 2024)
Endoplasmic reticulum stress occurs due to large amounts of misfolded proteins, hypoxia, nutrient deprivation, and more. The unfolded protein is a complex intracellular signaling network designed to operate under this stress. Composed of three individual arms, inositol-requiring enzyme 1, protein kinase RNA-like ER kinase, and activating transcription factor-6, the unfolded protein response looks to resolve stress and return to proteostasis. The CD8+ T cell is a critical cell type for the adaptive immune system. The unfolded protein response has been shown to have a wide-ranging spectrum of effects on CD8+ T cells. CD8+ T cells undergo cellular stress during activation and due to environmental insults. However, the magnitude of the effects this response has on CD8+ T cells is still understudied. Thus, studying these pathways is important to unraveling the inner machinations of these powerful cells. In this review, we will highlight the recent literature in this field, summarize the three pathways of the unfolded protein response, and discuss their roles in CD8+ T cell biology and functionality.